Tendering processes / Muhammad Haziq Zol Kapeli - Zol Kapeli, Muhammad Haziq (Universiti Teknologi MARA, Perak, 2022)
Tendering is a process by which governments and financial organizations solicit bids for significant projects that must be completed within a specific time frame. In its simplest form, tendering is the process by which an organisation who needs goods/services invites other parties to submit a proposal or bid to provide these goods/services. . However, currently there is limited research conducted on proper tendering process particularly involved two different sectors (government and private sector). The report will discuss the tendering process conducted for Bina Raya Construction & Plumbing at 29-2F, Jalan Setia Perdana U13/27b, Alam Nusantara, 40170 Shah Alam, Selangor. There are three objectives highlighted in this report, The first one is to identify an appropriate tender document for different class of contractors, second to determine the process of preparing tender and, finally to ascertain the problem occurred during the tendering process. Apart of that, the study is conducted using three method such as regularly interview session with the supervisor in charge, observation, and some documents reference. As a results, the tender document can be completed perfectly with any mistake. Nevertheless, during the tendering process, As a results, there are five tendering processes identified from this study. These are include looking for tenders’ advertisement, determine the specification, tender documentation, submission, and acceptance latter / contract awarded. In nutshell, knowing the proper tendering process will benefit to the contractor and the client in order to complete the tender document. As a result, it is hoped that additional contractors would use this suitable tendering process in the future when developing tenders for similar projects.